Acute care surgery and emergency general surgery: Addition by subtraction. Issue 1 (July 2016) - Bruns, Brandon Robert; Tesoriero, Ronald B.; Narayan, Mayur; O'Meara, Lindsay; Lauerman, Margaret H.; Eaton, Barbara; Herrera, Anthony V.; Scalea, Thomas Michael; Diaz, Jose J.
Abstract : INTRODUCTION: The formation of Acute Care Surgery services leads to decreased time to treatment and improved outcomes for emergency general surgery (EGS) patients. However, minimal work has focused on the ideal care delivery system and team structure. We hypothesize that the implementation of a dedicated EGS team (separate from trauma and surgical critical care), with EGS-specific protocols and dedicated operating room (OR) time, will increase productivity and improve mortality. METHODS: This is a retrospective review of financial and EGS registry data from fiscal year (FY) 12 to FY15. Data are from an academic, university-based EGS team composed of two acute care surgery attending surgeons, advanced practitioners (APs), residents, and a fellow. In FY12, processes were implemented to standardize paging of consults, patient sign-out with attending surgeons' and APs' participation, clinical/billing protocols, OR availability, and quality improvement. Outcomes included relative value units (RVUs), surgical case volume, charges/payments, and number of patient encounters. The secondary outcome was mortality. The χ 2 test was used to compare mortality, and p < 0.05 was considered significant. RESULTS: Total patient encounters increased from 6, 723 in FY 12 to 9, 238 in FY 15 (+37%). Relative value units increased from 18, 422 in FY 12 to 25, 314 in FY 15 (+37%). Charges increased by 76% and payments increased by 60% from FY 12 to FY 15. Charges per encounter increased from $461 in FY 12 to $591 in FY 15 (+28%) Additionally, both inpatient and surgical case loads increased. Mortality remained stable throughout the study period (FY 12, 4.5%; FY 13, 5.2%; FY 14, 5.3%; FY 15, 3.2%: p = 0.177). CONCLUSIONS: Implementation of dedicated OR time, defined EGS team structure, practice protocols, and active attending surgeons'/APs' participation was temporally related to increased case volume, patients seen, and revenue, while mortality remained unchanged. Further study is necessary to establish the translatability of these data to other systems. LEVEL OF EVIDENCE: Economic/decision, level III.